Status of Wood Preservation in India - Gairola, Suresh; Aggarwal, Pankaj (Indian Forester, 2005)
Wood, despite the advent of other modern materials, continues to play an important role in man’s day to day life. Usage of wood ranges from fuel wood to engineered wood products and demand for it is increasing which has resulted in depletion of forests and diminiShing wood supplies. Future needs will mainly be required to be met from plantation timbers after adopting processing technologies for their life enhancement. Preservation treatment can reduce timber requirement because of enhancing wood service life that can help in managing forsts on a sustainable basis to serve the dual purpose of providing a stable raw material supply and maintaining ecological balance. India has given to the world two of the most effectice and widely used wood preservatives viz. CCA and CCB. However, the present level of wood treatment in the country is very low with negligible contribution to the wood economy. Different institutions have made significant research contributions and generated tremendous data on wood prservation but because of lack of general awareness and enabling legislative support, usage of wood preservation has not taken off in the country. Compounding the problem is extremely weak industry-user group-research linkages.